2019
DOI: 10.1155/2019/8105138
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Seed Germination and Seedling Development of a Rare Indonesian Native Orchid Phalaenopsis amboinensis J.J.Sm

Abstract: Phalaenopsis amboinensis, an epiphytic orchid, has a great potential for commercial exploitation in the cut-flower industry. It is difficult to propagate vegetatively as it naturally grows slowly. Therefore, there is a need to improve the propagation methods to avoid endangering its natural populations. The objective of this study was to identify the best medium and organic supplements for seed germination and plantlets development of P. amboinensis. Seeds from 4-month-old hand-pollinated orchids were sown on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 31 publications
2
16
0
3
Order By: Relevance
“…It was observed that 78.00% of the seeds germinated on agar solidified MS with 3% sucrose but without any PGR supplements. Similar results were obtained by Utami and Hariyanto (2019) in Phalaenopsis amboinensis J.J. Sm (orchid), Islam et al (2018) in Eustoma and Darso and Feyissa (2015) in Cordeauxia edulis. No report was available for germination of seeds of R. tetraphylla in MS.…”
supporting
confidence: 82%
“…It was observed that 78.00% of the seeds germinated on agar solidified MS with 3% sucrose but without any PGR supplements. Similar results were obtained by Utami and Hariyanto (2019) in Phalaenopsis amboinensis J.J. Sm (orchid), Islam et al (2018) in Eustoma and Darso and Feyissa (2015) in Cordeauxia edulis. No report was available for germination of seeds of R. tetraphylla in MS.…”
supporting
confidence: 82%
“…Gonçalves et al [49] found that the number of Hadrolaelia purpurata seedlings produced was the highest on KC medium containing 90 g•L −1 of BH. Furthermore, Utami and Hariyanto [50] observed the effect of supplementation with 150 mL•L −1 CW with different BH concentrations (0, 5, 10, 15 g•L −1 ) on the plantlet development of Phalaenopsis amboinensis and found that the organic supplementation of CW together with BH had significantly increased the growth of plantlets. Banana has often been used as an organic additive in in vitro cultures because of its high levels of potassium, manganese, calcium, sodium, iron, zinc, thiamin, riboflavin, niacin, pyridoxine, pantothenic acid, ascorbic acid, folic acid [86], and natural growth regulators such as zeatin, gibberellin, and IAA [87,88].…”
Section: Banana Homogenatementioning
confidence: 99%
“…The medium performance could be improved through addition of complex organic substance such as coconut water or tomato extract. Using said substances have successfully enhanced various orchid species growth (Zhang et al 2015;Dwiyani et al 2015;Setiari et al 2016;Utami et al 2017;Utami and Hariyanto 2019).…”
Section: Introductionmentioning
confidence: 99%